Impact of orphanhood on underweight prevalence in sub-Saharan Africa - Rivers, Jonathan; Mason, John; Silvestre, Eva; Gillespie, Stuart; Mahy, Mary; Monasch, Roeland (SAGE Publications, 2008)
In Africa, approximately 25 million people live with HIV/AIDS and 12 million children are orphaned. Although evidence indicates that orphans risk losing opportunities for adequate education, health care, and future employment, the immediate effects of orphanhood on child nutritional status remain poorly understood.This paper assesses the nutritional impact of orphanhood, with particular emphasis on taking account of various factors potentially confounding or masking these impacts.Child anthropometry and orphan status were examined in 23 Multiple Indicator Cluster Surveys and Demographic and Health Surveys throughout sub-Saharan Africa, which were subsequently merged into larger, region-specific datasets (East, West, and Southern Africa). To compare orphans and nonorphans, linear regression and probit models were developed, taking account of orphan status and type, presence of a surviving parent in the household, household structure, child age and sex, urban versus rural residence, and current wealth status.Few differences emerged between orphans and nonorphans in controlled and uncontrolled comparisons, regardless of orphan type, presence of surviving parent, or household structure. Age differentials did confound nutritional comparisons, although in the counterintuitive direction, with orphans (who were 8 months older on average) becoming less malnourished when age differences were taken into account. Wealth did appear to be associated with orphanhood status, although it did not significantly confound nutritional comparisons.Orphans were not consistently more malnourished than nonorphans, even when potential confounding variables were examined. Since household wealth status is likely to change after becoming affected by HIV, ruling out wealth as a potential confounder would require more detailed, prospective studies.